Designing content of professional training of future handicraft and technology teachers in organizing extracurricular artistic and technical activity of pupils - Androshchuk, Ihor (Professional Pedagogics, 2018)
The article analyses the main approaches to the concept of “content”. The experience of pedagogical reflection and the mastering of self-improvement techniques are distinguished as the most important components of the content. The focus is on two types of pedagogical designing, namely the adaptation of the content to social environment and its conditions (it realizes social requirements of society)  and the improvement  or transformation  of the content in accordance with educational goals, values and beliefs. The ways of designing the content    of future specialists’ training are defined as follows: linear, concentric, spiral ones. It is specified that the process of designing the content as part of the system of training future handicraft and technology teachers for organizing extracurricular artistic and technical activity  of pupils  requires  that the integrative  nature of educational subjects and their purposeful orientation towards the integral and systematic training for professional activity should be taken into account. It is clarified that the process of designing the content  of training future handicraft and technology teachers for organizing extracurricular artistic and technical activities of pupils involves three stages, namely the Target Stage, the Main Stage and the Identification and Correction Stage. It is noted that the Target Stage implementation results in the formulation of goals and outcomes of future handicraft and technology teachers’ training in accordance with social demands and requirements for professional activity of these specialists, which makes it possible to determine professional knowledge, abilities, skills and professionally important personal qualities.
Keywords: content of professional training; pedagogical designing; stages in designing; handicraft and technology teacher; extracurricular artistic and technical activity